The Ambivalences of English Lessons Existing in Indonesian Primary Schools - Yuli Astutik; Ahmad Munir (Institut Agama Islam Negeri Palopo, 2022)
This article discusses policies governing the English curriculum in Indonesian primary schools. English, as local content or as an extracurricular subject delegated to each school, creates inequality in primary school education as some primary schools offer English learning and many do not, for various reasons such as a lack of qualified human resources at TEYL, or insufficient facilities. This ambivalence eventually creates problems at the primary education level, including a lack of clarity regarding careers for English teachers in primary schools. This results in a limit on the number of tertiary institutions that provide English-teaching education for EYL, so that primary schools in turn employ classroom teachers who have no credentials to teach English in the classroom. This ambivalence would not have occurred if the government had made a firm decision on the existence of English as a subject in Indonesian primary schools. Therefore, the authors of this article make an argument for the importance of mastering English as an international language (EIL) for young learners in non-English-speaking countries, especially in this era of rapid technological development. This article suggests that the government should immediately establish a clear policy regarding the status of English as a primary school subject, and that the curriculum policy in primary schools should no longer designate English as a local content or extracurricular subject, but rather as a compulsory subject which automatically adjusts learning outcomes based on student demographic characteristics. The implication of this article is that English lessons can be taught to all young learners through an eclectic approach.Keywords: English as an international language; Government policy; Indonesian setting; teaching English to young learners